2018
DOI: 10.2147/ppa.s166332
|View full text |Cite
|
Sign up to set email alerts
|

Treatment preferences among Japanese women with dysmenorrhea: results from a discrete choice experiment study

Abstract: PurposeTo examine patient preferences for oral and intrauterine system treatments for dysmenorrhea in Japan.Patients and methodsA discrete choice experiment was conducted to assess the willingness to accept trade-offs among hypothetical treatment profiles. An internet-based survey was administered to women 18–49 years of age who self-reported a dysmenorrhea diagnosis or experienced dysmenorrhea at least once in the past 6 months (N=309). Choice questions included pairs of treatments presented with different at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…For example, Eastern cultures are more likely to use methods such as acupuncture and traditional remedies. In a study performed in Japan [ 42 ] on the treatment preferences of girls with dysmenorrhea, the data revealed that, despite the fact that self-medication was still at the top of preferred treatments (chosen by 58% of participants), 12% of the sample stated that they preferred being treated using traditional Chinese medicine, compared to less than 1% of the participants in our survey, who stated that they would use acupuncture.…”
Section: Discussionmentioning
confidence: 58%
“…For example, Eastern cultures are more likely to use methods such as acupuncture and traditional remedies. In a study performed in Japan [ 42 ] on the treatment preferences of girls with dysmenorrhea, the data revealed that, despite the fact that self-medication was still at the top of preferred treatments (chosen by 58% of participants), 12% of the sample stated that they preferred being treated using traditional Chinese medicine, compared to less than 1% of the participants in our survey, who stated that they would use acupuncture.…”
Section: Discussionmentioning
confidence: 58%
“…Their longterm use has been associated with common complications like headache, dizziness, drowsiness, loss of appetite, nausea, vomiting, gastrointestinal bleeding, increased acute asthma, dysuria, and acne. Comparable pain intensity of dysmenorrhea and renal colic has been reported by Akiyama et al [28] and Iacovides et al [29]. Chen et al [30] reported that dysmenorrhea is also associated with other pain conditions such as migraines, fibromyalgia (FM), and IBS.…”
Section: Mini Reviewmentioning
confidence: 77%
“…Dysmenorrhea leads to a loss of 140-million working hours yearly in the United States [26]. In Japan, economic losses as a result of dysmenorrhea were estimated to be 4.2 billion dollars annually [27].…”
Section: Discussionmentioning
confidence: 99%